2015
DOI: 10.1080/02626667.2014.965174
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of an at-site flood frequency analysis method for extreme events based on stochastic simulation of hourly rainfall

Abstract: Extreme events are rarely observed, so their analysis is generally based on observations of more frequent values. The relevance of flood frequency analysis (FFA) method depends on its capability to estimate the frequency of extreme values with reasonable accuracy using extrapolation. A FFA method based on stochastic simulation of flood event is assessed based on its reliability and stability. For such an assessment, different training/testing decompositions are performed for a set of data from more than 1,000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…In the present case, for a long return period, the low dependence between the regionalised SHYREG extreme quantiles and calibration discharge data provide quantile estimates relatively close to that obtained in a gauged configuration, i.e., quantiles that can be and have already been validated [18,45].…”
mentioning
confidence: 77%
See 4 more Smart Citations
“…In the present case, for a long return period, the low dependence between the regionalised SHYREG extreme quantiles and calibration discharge data provide quantile estimates relatively close to that obtained in a gauged configuration, i.e., quantiles that can be and have already been validated [18,45].…”
mentioning
confidence: 77%
“…Most of the time, operational FFAs are implemented by fitting a statistical distribution to local data in gauged sites or by estimating flood quantiles through empirical relationships called "rational" approaches [44]. Recent studies implemented a data-based comparison of diverse FFA methods used in France [9] and concluded that methods using regional data or exploiting the rainfall information should be preferred to purely at-site statistical data [18,45]. Nevertheless, the transfer of this kind of FFA method to ungauged catchments has remained limited with only one regionalisation method tested and the performance was insufficient to draw general conclusions [45].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations